Determinasi Risiko Prenatal terhadap Stunting Neonatal: (Studi di RSUD Dr. Soedarso Pontianak) - Pinda Hutajulu; Deli Theo; Ramadhani Syafitri Nasution (Jurnal Kesehatan Amanah, 2025)
Neonatal stunting is a form of growth failure that begins in the womb, marked by birth length below the 10th percentile, reflecting maternal nutritional and health status during pregnancy. This study aimed to analyze the influence of prenatal risk factors on neonatal stunting at Dr. Soedarso General Hospital, Pontianak. Using an institution-based cross-sectional design with a quantitative approach, the study utilized secondary data from maternal and newborn medical records collected from June to September 2024. A total of 485 mother–infant pairs were selected using purposive sampling based on inclusion and exclusion criteria. Independent variables included maternal age, height, anemia, hypertension during pregnancy, and parental education levels, while the dependent variable was neonatal stunting. Data were analyzed using Chi-square tests and logistic regression. The results showed a neonatal stunting prevalence of 23.9%, with maternal age under 20 years as the only significant risk factor (AOR = 2.54; p = 0.035). Other variables such as anemia, hypertension, maternal height, and parental education were not significantly associated with stunting. These findings indicate that teenage pregnancy is a critical factor in neonatal stunting prevention. Strengthening reproductive health education and antenatal care services for adolescent girls is essential to reduce the prevalence of stunting from the prenatal stage.